Pengaruh Efikasi Diri Terhadap Keberhasilan Pembelajaran Berbasis Web di Era Digital - Sriayu Sibarani; Agnes Yosefin Rajagukguk; Nengsi Tarihoran; Sony Rikson; Elsina Sihombing (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to examine the impact of self-efficacy on the success of web-based learning in the digital era. Self-efficacy, which refers to an individual's belief in their ability to overcome challenges, is believed to play a crucial role in achieving learning outcomes. In the rapidly evolving digital era, web-based learning has become an effective method for delivering materials flexibly and interactively. This research uses a quantitative approach with a survey method involving students from various universities. The results show that self-efficacy has a significant impact on the success of web-based learning. Students with higher self-efficacy tend to be more successful in completing tasks and understanding the learning material delivered through online platforms. This study recommends the importance of developing students' self-efficacy to enhance the effectiveness of web-based learning, especially in the context of education in the digital era.